The Future of Teacher Education Making: EFL Pre-Service Teachers and Teacher Educators' Perceptions of Professional Preparation - Mohammad Nabi Ranjbari; Hossein Heidari Tabrizi; Akbar Afghary (Journal of Modern Research in English Language Studies)
The student's success at school greatly depends on quality teacher and this has led to the governments' growing focus on the quality of teacher education programs and production of quality teachers. This study explored the key stakeholders' views of the pre-service teachers' professional preparation in the latest teacher education program.The participants were 257 BA students in TEFL and 40 teacher educators. Data were collected through an adapted version of the Survey of Teacher Education Programs (STEP) (Williams-Pettway, 2005) and semi-structured interview. After analyzing data by employing descriptive and inferential statistics, the findings indicated that the participants positively evaluated the components in the program and found it effective in preparation of prospective teachers. However, some participants pointed to some drawbacks as the requirement of more input on language proficiency and knowledge of English language learners, more effective use of technology, more teaching practice opportunities as a means of experiential learning, and sufficient support from supervising teachers and teacher educators during teaching practicum courses for student teachers. The findings from this study may help the tomorrow’s educational leaders and syllabus designers to equip themselves with a visionary perspective and begin to form ideas for future change and direction in line with social influences.